1989
DOI: 10.1002/bjs.1800761108
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis after renal transplantation

Abstract: Post-transplantation pancreatitis is an infrequent complication with a high risk of mortality. In a 7-year period, there were five patients who had documented pancreatitis out of a total of 488 renal homograft recipients, an incidence of 1 per cent. Two cases occurred in patients with an orthotopic transplant, one of them as a result of surgical injury of the pancreas and the other as a consequence of cytomegalovirus infection. The third case was an acute pancreatitis of hypercalcaemic origin, the fourth patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…The incidence of acute pancreatitis following renal transplantation varies from 1 to 5% [1][2][3]. Renal transplant recipients have multiple risk factors for pancreatitis making identification of a single etiological agent difficult in clinical setting (Table 1).…”
Section: Discussionmentioning
confidence: 98%
“…The incidence of acute pancreatitis following renal transplantation varies from 1 to 5% [1][2][3]. Renal transplant recipients have multiple risk factors for pancreatitis making identification of a single etiological agent difficult in clinical setting (Table 1).…”
Section: Discussionmentioning
confidence: 98%
“…2 In contrast, in a review of the literature of AP occurring in renal allograft recipients, both azathioprine and prednisone were documented to be etiologic factors. 20 Hagopian et al 21 have also suggested that increased doses of corticosteroids within 1 year of the episode can increase the mortality from AP in cardiac and renal allograft recipients.…”
Section: Discussionmentioning
confidence: 99%
“…22 This is in contrast to either no obvious cause or cytomegalovirus as precipitating factors for AP within the first 2 months after renal transplantation. 20,22 However, in the largest series reported of AP occurring in renal transplant recipients more than 2 months after allografting, immunosuppression was believed to be the most likely underlying factor because neither alcohol nor cholelithiasis were documented. 4 In conclusion, this study shows that the incidence of AP (3%) is low in stable adult transplant recipients post-OLT, and AP can occur many years after primary allografting.…”
Section: Discussionmentioning
confidence: 99%
“…It can also have a more aggressive course, with mortality ranging from 37.5% to 63% (2,3,6,7) and is observed in both adult and pediatric populations (8). AP has been well documented in the setting of solid organ transplantation and has been described following kidney, bone marrow, intestinal, and heart transplantation (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%